Immunogenicity of Intramuscular Fractional Dose of Inactivated Poliovirus Vaccine. (27th June 2019) - Resik, Sonia; Mach, Ondrej; Tejeda, Alina; Jeyaseelan, Visalakshi; Fonseca, Magile; Diaz, Manuel; Alemany, Nilda; Hung, Lai Heng; Aleman, Yoan; Mesa, Ileana; Garcia, Gloria; Sutter, Roland W
Abstract: Backgrounds: Intradermal (id) fractional inactivated poliovirus vaccine ([fIPV] one fifth of normal IPV dose) is safe and immunogenic; however, id administration is perceived as difficult. We compared fIPV immunogenicity administered id or intramuscularly (im). Methods: This noninferiority trial was conducted among polio vaccine-naive Cuban infants who received 2 IPV doses at 4 and 8 months of age. Infants were randomized into 4 arms: (A) fIPV, 0.1 mL im; (B) fIPV, 0.2 mL im; (C) fIPV, 0.1mL id; and (D) IPV, 0.5 mL im. Blood collected before and after vaccinations was tested for poliovirus-neutralizing antibodies. Results: A total of 196 of 214 (91.6%) enrolled children completed study. Seroconversion after 2 IPV doses in each arm were as follows: (A) 97.3% (90.6–99.7), 98.7% (92.7–99.9), and 90.5% (81.5–96.1) for serotypes 1, 2, and 3, respectively; (B) 97.2% (90.3–99.7), 100%, 95.8% (88.3–99.1) for serotypes 1, 2, and 3, respectively; (C) 89.3% (71.8–97.7), 92.9% (76.5–99.1), 82.1% (63.1–93.9) for serotypes 1, 2, and 3, respectively; and (D) 100%, 100%, 100% for serotypes 1, 2, and 3, respectively. Seroconversion with fIPV im was noninferior to fIPV id for all serotypes. Conclusions: We demonstrated noninferiority of fIPV im compared with id when administered at 4 and 8 months of age. Further investigations in an earlier infant schedule should be pursued to explore fIPV im as option for dose-sparing strategy in countries reluctant to use fIPV id due to programmatic difficulties of id administration.